Can sodium silicates affect collagen structure during tanning? Insights from small angle X-ray scattering (SAXS) studies. Issue 19 (16th February 2017) - Zhang, Yi; Ingham, Bridget; Leveneur, Jérôme; Cheong, Soshan; Yao, Yin; Clarke, David J.; Holmes, Geoff; Kennedy, John; Prabakar, Sujay
Abstract : Sodium silicates can pseudo-stabilize collagen molecules during leather processing by preventing collagen molecules from undergoing conformational changes due to the silica coating on the fibrils. Abstract : The effect of sodium silicates on collagen structure during leather processing was investigated. Small angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC) reveal that the molecular structure and thermal stabilities of the sodium silicate treated leathers (So-Si and So-Si + BCS) were different to the conventionally processed chromium treated leathers (BCS). The collagen fibrils were observed to be coated by aggregates of silica, which did not affect the axial periodicity ( D -period) of the collagen molecules. However, an increase in collagen fibril diameter was observed during the main tanning step when sodium silicates were used. This could be due to the swelling of collagen fibers from the high alkaline conditions of sodium silicates. From DSC studies, it was also found that sodium silicate treated samples impart no effect on collagen stabilization in the absence of chromium(iii ). However, a pseudo-stabilization effect is observed in the So-Si + BCS samples, possibly due to the inability of the collagen molecules to undergo conformational changes due to the silica coating on the collagen fibrils.